A defence of the standard conception of adversary advocacy - Sutherland, Roland (My University, 2016)
The standard conception of adversary advocacy postulates that lawyers be partisan towards clients, within the limits of law, and be unaccountable for the client’s lack of integrity. Thus, lawyers owe duties to both clients and judges. Partisanship requires lawyers to conceal from judges confidential information received from clients and to advance arguments they believe are incorrect. Thus, say critics, the standard conception permits lying and cheating. This essay refutes that proposition. It is argued that truth-seeking is merely instrumental in the legal system and what is sought is ‘proof.’ The standard conception is defended, albeit with a corrective emphasis on balancing partisanship with duties to promote effective judicial decision-making. Counsel’s role is defined as a licensed fiduciary intermediary, who by non-disclosures and insincere arguments acts morally because such practises promote the legitimacy of the legal system and uphold client dignity. The contending views of leading proponents and antagonists of the standard conception are examined.
A research Report submitted to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Arts, Applied Ethics for Professionals Johannesburg, 2016
Keywords: Legal ethics